1997
DOI: 10.3758/bf03206022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perceptual context on transsaccadic visual matching

Abstract: Transsaccadic visual matching refers to the phenomenon in which presaccadic signals at the location ofthe saccade goal influence the visibility ofpostsaccadic test signals presented at the fovea (Juttner & Rohler, 1993).The present study uses variations ofthe perceptual context, provided by the structure of the presaccadic stimulus display, to investigate the influence of spatial information, decision factors, and visual attention on this form of transsaccadic information processing. The experiments yielded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Within a single fixation, presaccadic information should be updated and be available directly after the saccade. In Chapter 2, we demonstrate a direct link between the motion information in the presaccadic and immediate post-saccadic information, as hypothesized from the results earlier studies (Deubel, Bridgeman, & Schneider, 1998;Jüttner, 1997). However, it has been suggested that spatiotopic updating can only be observed when the saccade can be planned for 500 ms or more Zimmermann, Morrone, Fink, et al, 2013).…”
Section: Time Course Of Spatiotopic Updatingsupporting
confidence: 74%
See 2 more Smart Citations
“…Within a single fixation, presaccadic information should be updated and be available directly after the saccade. In Chapter 2, we demonstrate a direct link between the motion information in the presaccadic and immediate post-saccadic information, as hypothesized from the results earlier studies (Deubel, Bridgeman, & Schneider, 1998;Jüttner, 1997). However, it has been suggested that spatiotopic updating can only be observed when the saccade can be planned for 500 ms or more Zimmermann, Morrone, Fink, et al, 2013).…”
Section: Time Course Of Spatiotopic Updatingsupporting
confidence: 74%
“…Second, spatiotopic updating can develop quickly. Specifically, the results show that post-saccadic perception immediately after saccade offset is influenced by the pre-saccadic stimulus (Deubel et al, 1998;Fornaciai et al, 2018;Jüttner, 1997). Moreover, in the integration of pre-and post-saccadic visual information, the weight of the pre-saccadic stimulus -this stimulus is presented in the peripheral visual field, and earliest in time -is lower than that of the post-saccadic stimulus…”
Section: Spatiotopic Updating Reflected In Behaviourmentioning
confidence: 88%
See 1 more Smart Citation
“…However, concerning the aspect of spatial generalization, that is, the application of previously learned concepts across the visual field, the situation is different. Further support comes from observations concerning the transsaccadic processing of visual information ( Jüttner & Röhler 1993;Jüttner 1997). The finding of a partial generalization of learned categorical concepts stands in contrast to the failure to obtain shift-invariance concerning the discrimination of random binary patterns (Nazir & O'Regan 1990).…”
Section: Martin Jüttnermentioning
confidence: 99%
“…Within a single fixation, presaccadic information should be updated and be available directly after the saccade. Concerning the postsaccadic availability, different experiments demonstrated that spatiotopic updating primarily affects perception immediately after saccades (20,(34)(35)(36). However, concerning the presaccadic updating of visual information, spatiotopic representations have been estimated to develop surprisingly slowly, requiring fixation durations of more than 500 ms (37)(38)(39)(40)(41).…”
mentioning
confidence: 99%